2021
DOI: 10.3390/plants10102153
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal Activity of Silver Nanoparticles Biosynthesized with Beech Bark Extract

Abstract: Biosynthesis is a green method for the synthesis of silver nanoparticles (AgNPs). This study aimed to assess the antifungal activity of two silver nanoparticle solutions, synthesized using beech bark extract (BBE) and acetate and nitrate silver salts (AgNP Acetate BBE and AgNP Nitrate BBE), their influence on biofilm production, their potential synergistic effects with fluconazole, on different Candida spp., and their influence on virulence factors of C. albicans (germ tube production, gene expression for ALS3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 61 publications
(86 reference statements)
1
9
0
Order By: Relevance
“…Similarly, the biosynthesized AgNPs using the seed extract of Syzygium cumini displayed anti-candidal activity at 0.125-0.250 mg/mL [42]. AgNPs biosynthesized by beech bark extract showed MIC of 0.03 mg/mL against C. albicans [43]. Furthermore, AgNPs synthesized by Caesalpinia ferrea extract displayed MIC values in the range of 156.25-1,250 µg/mL against C. albicans, C. glabrata, C. kruzei, and C. guilliermondii [44].…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, the biosynthesized AgNPs using the seed extract of Syzygium cumini displayed anti-candidal activity at 0.125-0.250 mg/mL [42]. AgNPs biosynthesized by beech bark extract showed MIC of 0.03 mg/mL against C. albicans [43]. Furthermore, AgNPs synthesized by Caesalpinia ferrea extract displayed MIC values in the range of 156.25-1,250 µg/mL against C. albicans, C. glabrata, C. kruzei, and C. guilliermondii [44].…”
Section: Discussionmentioning
confidence: 96%
“…The lyophilized IL-6 was reconstituted, according to the manufacturer's instructions, to achieve in vitro physiological final value of 250 pg/ml, comparable with achievable human serum concentrations during infections (range between 0 and 552.6 pg/ml) [10]. The experiments were performed in triplicate, based on previously published protocols [11,12]. As follows, the used methods are described shortly.…”
Section: Methodsmentioning
confidence: 99%
“…In-depth attempts at elucidating the molecular action of silver NPs were described in the study of Mare, A.D. et al The same synthesis principle was maintained by using the beech bark extracted from Fagus sylvatica L. Nanoparticles synthesis was performed following two pathways that consisted of using two solutions of 1mM, namely AgNO 3 and CH 3 -COOAg solutions. It was revealed that the nanoparticulate products prepared with the acetate solution caused the downregulation of SAP2 expression, which is known to be involved in host cell invasion [ 174 ]. To further complete the mechanistic map of silver NPs, Jia D. and Sun W. focused their attention on the synergistical effect of the nanoparticles and fluconazole to suppress C. albicans activity.…”
Section: Biomaterials and Nanotechnological Approachesmentioning
confidence: 99%